Effect of Water Content on the Impact Propensity of White Sandstone - Jiankui Bai; Chuanming Li; Ruimin Feng; Nan Liu; Xiang Gao; Zhengrong Zhang; Bochao Nie (Geofluids)
Impact ground pressure is one of the most common dynamic disasters induced by mining activities, and water content is an important factor affecting such dynamic disasters. In this paper, uniaxial compression test, cyclic loading and unloading test, and acoustic emission test were conducted on white sandstone using RMT-150B rock mechanics test system and DS5 acoustic emission test system. The influence law of water content was analyzed on the strength characteristics, energy change characteristics, and impact propensity of white sandstone. The results showed that (1) the internal structure of the sandstone gets softened with the increase of the water content. The cohesive effect within the rock also begins to weaken, which in turn reduces the stiffness of the material and enhances its plasticity. The ability of the rock to resist elastic deformation becomes weaker, resulting in lower compressive strength and elastic modulus when the rock is subjected to external forces, making it more prone to deform and fail. The decrease in compressive strength of the water-saturated rock is 33.3%, and the decrease in its elastic modulus is 28.1% compared to the dry rock. (2) As the water content increases, the cohesion of the rock decreases and the internal structure of the rock fails more easily, which ultimately makes the energy needed for rock destruction lower. As a result, the total energy, elastic energy, and dissipative energy of the rock are reduced. The accumulated AE energy also decreases with the increase of the water content, indicating that rocks with higher water content gather less elastic energy before damage and accumulate less energy when deformation damage occurs. (3) The impact energy index and elastic energy index are negatively correlated with the water content. The impact energy index is reduced by 28.6%, and the elastic energy index is reduced by 20.9% for the saturated rock compared to the dry rock. The elastic energy index and impact energy index both decrease with the increase of rock water content, indicating that the less elastic energy is stored before the destruction of the rock and no excess energy is transformed into energy in rock crushing when the rock breaks, and therefore, the impact propensity of the rock is smaller. The results of the study can provide a theoretical basis for underground construction as well as rock fracture destabilization.